Analysis Of The Concept Of Taklik Talak According To The Syafi'i School Of Thought And Law No. 1 Of 19741 OF 1974 - fadli ardiansah, muhammad; Hambari,; Salati Asmahasanah, (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
This research discusses the concept of taklik talak from the perspective of the Shafi'i Mazhab and its comparison with the provisions in Law No. 1 of 1974 concerning Marriage in Indonesia. Taklik talak is a conditional agreement pronounced by the husband after the marriage contract, which stipulates the fall of divorce if certain conditions are violated by the wife. In the Syafi'i Mazhab, taklik talak is automatic if the conditions are met, without the need for a judicial process. Meanwhile, in the Indonesian positive legal system, the implementation of talak must go through a religious court decision to be legally valid. This research uses a qualitative approach with a literature study method, examining classical sources in the Syafi'i Mazhab as well as legislation in Indonesia. The results of the research show that there are similarities in purpose, namely, as a form of protection for women's rights in marriage. However, both have fundamental differences in the aspects of implementation and legal force between the two legal systems. This study is expected to contribute to the harmonization between Islamic law and positive law and become a reference for academics and legal practitioners in handling divorce cases related to talaq.